2013
DOI: 10.1038/nchem.1645
|View full text |Cite
|
Sign up to set email alerts
|

Heterogenized cobalt oxide catalysts for nitroarene reduction by pyrolysis of molecularly defined complexes

Abstract: Molecularly well-defined homogeneous catalysts are known for a wide variety of chemical transformations. The effect of small changes in molecular structure can be studied in detail and used to optimize many processes. However, many industrial processes require heterogeneous catalysts because of their stability, ease of separation and recyclability, but these are more difficult to control on a molecular level. Here, we describe the conversion of homogeneous cobalt complexes into heterogeneous cobalt oxide catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
457
2
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 666 publications
(481 citation statements)
references
References 47 publications
10
457
2
8
Order By: Relevance
“…Similarly, pyrolyzed metal salts on carbon without any phenanthroline ligand present gave only slight conversion (Table 1, entries 22-28). Notably, pyrolysis of metal-phenanthroline complexes showed varying catalytic activities (Table 1 [32][33][34][35]. To demonstrate the recycling of the catalyst, Co 3 O 4 -NGr/C was used for the benchmark reaction.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, pyrolyzed metal salts on carbon without any phenanthroline ligand present gave only slight conversion (Table 1, entries 22-28). Notably, pyrolysis of metal-phenanthroline complexes showed varying catalytic activities (Table 1 [32][33][34][35]. To demonstrate the recycling of the catalyst, Co 3 O 4 -NGr/C was used for the benchmark reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Last year, we reported the preparation of nanoscale cobalt and iron oxides, which constitute excellent catalysts for highly selective hydrogenation process 33,34 . We also showed that pyrolysis of metal acetatenitrogen ligated complexes on carbon leads to the formation of nanoscale metal oxides (Co 3 O 4 -NGr/C; Fe 2 O 3 -NGr/C), which are surrounded by nitrogen-doped graphene layers (NGr).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Commercially, the reduction of nitroaromatics carried out in the gas phase using a nickel, copper or iron catalyst in the presence of various proton sources produces a large amount of wastes, which are environmentally undesirable [6]. In addition, high temperature and hydrogen pressure are other restrictions associated with these catalytic processes [7]. The classical methods for the hydrogenation of nitro compounds use various homogeneous transition-metal catalysts, e.g., Pd, Pt, Ru, etc.…”
Section: Open Accessmentioning
confidence: 99%
“…Ni, Co, Fe and Cu metals or oxides). [47][48][49][50][51][52] To take advantage of these characteristics and also as a part of our ongoing research programme on the design of new catalysts for the development of useful and green synthetic methodologies, [15,16,[53][54][55][56][57][58][59] herein, we report a dendritic magnetic catalyst based on Ni(0) nanoparticles, an inexpensive non-noble metal, for selective hydrogenation of nitro and nitrile compounds in the presence of various reducible substituents such as carboxylic acid, ketone, aldehyde and halogen to the respective amines using NaBH 4 as the reducing agent in the aqueous phase. …”
Section: Introductionmentioning
confidence: 99%